2018
DOI: 10.1111/dpr.12346
|View full text |Cite
|
Sign up to set email alerts
|

Are cash transfers the answer for child nutrition in sub‐Saharan Africa? A literature review

Abstract: Early evidence is ambiguous on the effects of cash transfer programmes on children, but until the last few years there has been little focus on Africa. We review the literature on 20 cash transfer schemes, including 12 from sub‐Saharan Africa. Such interventions have shown improvements in household diet and, in some cases, to agriculture, but have not always improved child health. However, a larger perspective focusing on two key time periods for nutrition—adolescence and the first 1,000 days of life reveals m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 67 publications
2
14
0
Order By: Relevance
“…The one metaanalysis evaluating 15 programmes in 10 countries demonstrated a minor but statistically insignificant impact on child anthropometry (Manley et al, 2013), echoing the lack of conclusive results across all reviews. Two recent articles specifically focus on the SSA region: Manley and Slavchevska (2019) and Owusu-Addo et al (2018). Both reviews reach similar conclusions as above.…”
Section: Cash Transfers and Child Nutrition Outcomessupporting
confidence: 59%
See 2 more Smart Citations
“…The one metaanalysis evaluating 15 programmes in 10 countries demonstrated a minor but statistically insignificant impact on child anthropometry (Manley et al, 2013), echoing the lack of conclusive results across all reviews. Two recent articles specifically focus on the SSA region: Manley and Slavchevska (2019) and Owusu-Addo et al (2018). Both reviews reach similar conclusions as above.…”
Section: Cash Transfers and Child Nutrition Outcomessupporting
confidence: 59%
“…From an academic perspective, the direct relation between CTs and child nutrition has been widely studied. In fact, several systematic reviews have been published in recent years (for example Fernald et al (2012), Leroy et al (2009), Manley and Slavchevska (2019), Owusu-Addo and Cross (2014), Owusu-Addo et al 2018, Pega et al (2017)). However, the results of these studies are mixed, and several authors point to the need to better understand the pathways through which CT programmes might work to improve nutritional status.…”
Section: Relevance and Contribution Of The Thesismentioning
confidence: 99%
See 1 more Smart Citation
“…Besides providing multiple benefits, there is a dearth of studies that incorporate the CCTs in an organized way and thus exploring the impact of the CCT programs on the educational wellbeing of youth. There are only a few studies elucidating the CCTs like Manley and Slavchevska [13] who worked as a meta-analysis to understand the effect of CCT programs on health status. Therefore, the researchers felt a dire need to give input to the literature on CCTs and thus evidencing the phenomenon in a developing country, Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Ferré and Sharif (2014) did not find a significant impact on the incidence of stunting and underweight in Bangladesh's Shombhob Pilot Project. By reviewing 20 articles in cash transfer programs (including 12 from Sub-Saharan Africa), Manley and Slavchevska (2016) concluded that cash transfers have not always improved child health.…”
Section: Introductionmentioning
confidence: 99%